Photoinduced Olefin Diamination with Alkylamines. (9th June 2020) - Govaerts, Sebastian; Angelini, Lucrezia; Hampton, Charlotte; Malet‐Sanz, Laia; Ruffoni, Alessandro; Leonori, Daniele
Abstract: Vicinal diamines are ubiquitous materials in organic and medicinal chemistry. The direct coupling of olefins and amines would be an ideal approach to construct these motifs. However, alkene diamination remains a long‐standing challenge in organic synthesis, especially when using two different amine components. We report a general strategy for the direct and selective assembly of vicinal 1, 2‐diamines using readily available olefin and amine building blocks. This mild and straightforward approach involves in situ formation and photoinduced activation of N‐chloroamines to give aminium radicals that enable efficient alkene aminochlorination. Owing to the ambiphilic nature of the β‐chloroamines produced, conversion into tetra‐alkyl aziridinium ions was possible, thus enabling diamination by regioselective ring‐opening with primary or secondary amines. This strategy streamlines the preparation of vicinal diamines from multistep sequences to a single chemical transformation. Abstract : All in one : Direct olefin diamination with alkylamines was achieved by using a photoinduced radical‐to‐polar crossover strategy. This approach enables the programmable and sequential addition of complex amine building blocks across olefins in a single chemical transformation. This operationally simple process has broad functional‐group compatibility and enables the use of advanced building blocks for the preparation of drug‐like small molecules.